Psychological and psychosocial interventions for cannabis cessation in adults: A systematic review. (3rd March 2016) - Chatters, Robin; Cooper, Katy; Day, Ed; Knight, Matt; Lagundoye, Olawale; Wong, Ruth; Kaltenthaler, Eva
Abstract: Objective : Many psychological and psychosocial interventions have been developed to treat regular users of cannabis, but it is unclear which intervention(s) are the most effective. This article aims to assess the effectiveness of psychological and psychosocial interventions for cannabis cessation, and to outline priorities for future research. Methods : A systematic review of the scientific literature. Eleven databases were searched in February 2014. Results : Twenty-six RCTs were identified; the majority were considered to be at a high risk of bias. Cognitive behavioural therapy (CBT) significantly improved outcomes compared with wait-list in five studies post-treatment, maintained at 9 months in the one study with later follow-up. Studies of motivational interviewing (MI) or motivational enhancement therapy (MET) gave mixed results, with some improvements over wait-list while some comparisons were not significant. Four studies comparing CBT against MI/MET gave mixed results; longer courses of CBT provided some improvements over shorter MI. Courses of other types of therapy (social support groups and case management) gave similar improvements to CBT. Vouchers for abstinence (contingency management) gave promising results in the short-term and at follow-up. Conclusion : Studies were heterogeneous, covering a range of interventions, comparators, populations and outcomes. CBT improved short-term outcomes in a clinically dependent self-selected population of cannabis users. Brief MI improved short-term outcomes at post-treatment in a younger non-clinically dependent population. There is some evidence that CBT may be more effective than briefer MI interventions although results were mixed. Contingency management may enhance long-term outcomes in combination with CBT in clinically dependent individuals.